Application of Microwave Ablation Combined With Chai Hu Qing Gan Tang in the Treatment of Idiopathic Granulomatous Mastitis - Hang Li; Bing Li; Haiying Chen; Xiaoli Liu; Hongling Wang; Guoliang Zhang (The Breast Journal)
Conclusion: The combination of CHQGT and MWA is comparable in overall therapeutic efficacy to the combination of glucocorticoids and MWA. However, the CHQGT and MWA combination is superior in reducing lump size, alleviating patient pain and accelerating recovery.